"Faces on a screen": A qualitative study of the virtual and in‐person conference experience. Issue 6 (20th December 2022) - Gottlieb, Michael; Sebok‐Syer, Stefanie S.; Bawden, Abigail; Shah, Meeta; Jordan, Jaime
Abstract: Introduction: The strengths and weaknesses of virtual and in‐person formats within continuing professional development (CPD) are incompletely understood. This study sought to explore attendees' perspectives across multiple specialties regarding benefits and limitations of conference formats and strategies for successful virtual and hybrid (i.e., in‐person conferences with a virtual option) conferences. Methods: From December 2020 to January 2021, semistructured interviews were conducted with participants who attended both virtual and in‐person CPD conferences. Purposive sampling was utilized to ensure diverse representation of gender, years in practice, location, academic rank, specialty, and practice type. Multiple specialties were intentionally sought to better understand the broader experience among physicians in general, rather than among a specific specialty. Using modified grounded theory approach with a constructivist–interpretivist paradigm, two investigators independently analyzed all interview transcripts. Discrepancies were resolved by in‐depth discussion and negotiated consensus. Results: Twenty‐six individuals across 16 different specialties were interviewed. We identified three overarching concepts: motivations to attend conferences, benefits and limitations of different conference formats, and strategies to optimize virtual and hybrid conferences. Specific motivators included both professional and personal factors. Benefits of in person included networking/community, immersion, and wellness, while the major limitation was integration with personal life. Benefits of virtual were flexibility, accessibility, and incorporation of technology, while limitations included technical challenges, distractions, limitations for tactile learning, and communication/connection. Benefits of hybrid included more options for access, while limitations included challenges with synchrony of formats and dilution of experiences. Strategies to improve virtual/hybrid conferences included optimizing technology/production, facilitating networking and engagement, and deliberate selection of content. Conclusions: This study identified several benefits and limitations of each medium as well as strategies to optimize virtual and hybrid CPD conferences. This may help inform future CPD conference planning for both attendees and conference planners alike.